Clinical profile of individuals with bisphosphonate-related osteonecrosis of the jaw: an integrative review - Maciel, Aloizio Premoli; Quispe, Reyna Aguilar; Martins, Lázara Joyce Oliveira; Caldas, Rogério Jardim; Santos, Paulo Sérgio da Silva (São Paulo Medical Journal, 2020)
BACKGROUND: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is still the most prevalent type of osteonecrosis with clinical relevance. In Brazil, bisphosphonate use is high but there is a lack of epidemiological studies on BRONJ. OBJECTIVE: To determine the clinical profile of BRONJ in a Brazilian population through an integrative review. DESIGN AND SETTING: Integrative review of BRONJ in a Brazilian population. METHODS: Cases and clinical research on Brazilians with BRONJ between 2010 and 2019, indexed in PubMed/MEDLINE, Scopus, Web of Science and LILACS were reviewed. Age, sex, type and time of bisphosphonate intake, administration route, related diseases, region of the BRONJ, diagnostic criteria, staging, triggering factor and type of treatment were analyzed. RESULTS: Fifteen articles on 128 subjects were included. Most patients were women (82.03%); the mean age was 63 years. Intravenous zoledronic acid was mostly used (62.50%), for breast cancer treatment (46.87%). The main localization of BRONJ was the mandible (54.68%), associated mainly with tooth extractions (45.98%). The diagnostic criteria were clinical (100%) and radiographic (89.06%), mostly in stage II (68.08%). The surgical treatments were sequestrectomy (37.50%) and platelet-rich plasma (PRP) (36.71%). Microbial control was done using chlorhexidine (93.75%) and infection control using clindamycin (53.90%). CONCLUSIONS: BRONJ had higher prevalence in Brazilian women receiving treatment for breast cancer and osteoporosis. The mandible was the region most affected with a moderate stage of BRONJ, particularly when there were histories of tooth extraction and peri-implant surgery. Sequestrectomy with additional drugs and surgical therapy was the treatment most accomplished.